E-collaborations and virtual organizations - Fong, Michelle W. L.; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Ave., Hershey, PA, 17033, USA), 2004)
E-Collaboration promotes interaction between people over the Internet, and is vital in virtual organization arrangements where people co-exist or work together, independent of time and location. E-Collaborations and Virtual Organizations covers a broad range of topics, from underlying technological structures to fundamental mechanisms that are relevant to e-Collaboration and virtual organizations. The chapters in this book present some of the current work in the field and represent a resource upon which knowledge, lessons, and views can be drawn upon for consideration and applications in the virtual world.
Knowledge sharing infrastructure and methods for virtual enterprises -- Workplace e-collaboration in practice -- Using web services in business-to-business integration -- Peer-to-peer corporate resource sharing and distribution with Mesh -- Collaborative engineering communities -- Strategic use of virtual organization -- Successful virtual organizations as collaboration networks -- Virtualization as a process of transformation of small and medium enterprises (SMEs) in the global virtual organization -- Impact of activities in the virtual environment -- Seamless multiparty videoconference -- ITFG : design and experience with a groupware system -- E-school administration systems.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Title from ebook home page (viewed on Sept. 10, 2010).
Keywords: Virtual work teams; Virtual reality in management; Virtual corporations -- Management; Electronic books